(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the implementation of the public entity Regional Health Foundation (Funsaude), as a new public program, in the state of Ceara. Methodology: this study was carried out based on two secondary data sources, namely the Saude Digital system of the Health Department of the State of Ceara-Brazil, from January 2020 to September 2022 and the Management Report of the Regional Foundation of Health from April to September 2022. The Logic Model was used to frame and assess the scope of the institution’s objectives. Trend linear regression and log-log multivariate regression analyzes were performed to develop an explanatory model with ten performance indicators. Results: Linear trends were found in five of the ten indicators studied. Considering the explanatory model (p-values < 0.001 and adjusted R2= 0.691), it was observed how percentagem variations in length of stay and in the number of emergency room admissions impact the occupancy rate. The indicators of the logic model linked to Funsaude’s objectives were presented. Conclusion: The proposed objectives were achieved by applying an evaluation model for na institution in the health area still in the implementation phase and proposing indicators capable of measuring the achievement of its results established in the creation phase.